Overview Of Physical Conditions (Vo2max) In The Paal 5 Basketball Love Community Of Jambi - Indrayana, Boy; Hasibuan, Mhd Usni Zamzami (Program Studi Pendidikan Kepelatihan Olahraga Fakultas Ilmu Pendidikan Universitas Bhayangkara Jakarta Raya, 2021)
The purpose of this study was to determine the physical condition of the paal 5 Jambi basketball lover community with the existing conditions without giving prior treatment. This research is a type of descriptive research. This study specifically aims to determine the level of physical condition of each individual who plays basketball in the basketball community regularly at night, which is related to aerobic endurance (VO2Max). The research instrument used was the MFT (Multi Fitness Test) test. The population used in this study were all members of the paal 5 basketball lover community as many as 20 people. Based on the results of the tests carried out, the results of the aerobic endurance test (VO2Max) were obtained with an average of 35.35 for all individuals and according to standardized norms, it was in the medium category. The average results obtained from each individual indicate that the physical condition of the basketball lover community is in the moderate category. These results mean that in order to achieve good physical condition it is necessary to carry out aerobic endurance training and other endurance exercises on a regular basis.